Influence of bronchopulmonary dysplasia on lung function in adolescents who were born extremely prematurely. Issue 12 (26th September 2022) - Harris, Christopher; Morris, Samuel; Lunt, Alan; Peacock, Janet; Greenough, Anne
Abstract: Objectives: To assess if a previous diagnosis of bronchopulmonary dysplasia (BPD) was associated with poorer lung function at 16 to 19 years of age, regardless of whether postnatal corticosteroids had been administered. Working Hypothesis: Infants with BPD will have poorer lung function at 16 to 19 years of age. Study Design: Prospective follow‐up study. Patient‐Subject Selection: One hundred and sixty‐one participants aged between 16 and 19 years who were born at less than 29 weeks of gestation; 87 had had BPD. Methodology: Lung function was assessed by spirometry (FEV1, FVC, FEV1 /FVC, FEF75, FEF50, FEF25, FEF25 –75, PEF), impulse oscillometry (R5Hz and R20Hz), plethysmography (FRCpleth, TLCpleth, RVpleth ), diffusion capacity of the lungs for carbon monoxide (DL CO, DL CO/VA) and lung clearance index (LCI). Questionnaires were used to quantify respiratory symptoms and a shuttle sprint test to assess exercise capacity. Results: At 16 to 19 years, those who had had a diagnosis of BPD had poorer airway function (FEV1, FEF75, FEF50, FEF25 –75 ) compared to those without. FVC and DL CO were also poorer in those who had BPD. Those differences remained significant after adjusting for sex, gestational age, and maternal smoking. When excluding those who had received postnatal corticosteroids, differences remained significant in FEV1, FVC, and FEF75 . There were no significant differences in exercise capacity or respiratory symptoms between those with and without BPD. Conclusions: In adolescents and young adults born prematurely, those who had BPD had poorer lung function compared to those without, regardless of whether they had received postnatal corticosteroids.